The Role of the Village Secretary in the Management of Village Government Programs in Sukamulya Village, Cikeusik District, Pandeglang Regency - Nita Suryaningsih; Viyulia Viyulia; Aan Apandi (HK-Publishing, 2025)
This research is motivated by the crucial role of the Village Secretary in supporting village governance, particularly in the management of village government programs. The Village Secretary is tasked with assisting the Village Head in areas such as administrative governance, planning, program coordination, and the preparation of accountability reports. This study employs a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and document analysis. Research informants—selected using purposive sampling—included the Village Head, the Village Secretary, village officials, the Head of the Village Consultative Body (BPD), and community leaders. The findings indicate that the Village Secretary's role in managing village government programs in Sukamulya Village, Cikeusik District, Pandeglang Regency, has been performed effectively. The Village Secretary plays a key role in assisting the Village Head with administrative governance, coordinating village officials, preparing planning and reporting documents, and supporting the implementation of village government programs. Factors facilitating this role include strong cooperation among village officials, support from the Village Head, effective communication, community participation, and orderly administration. Conversely, obstacles encountered include a heavy administrative workload, limited human resources, regulatory changes, and suboptimal community participation across the various stages of village government program management. Keywords: Role of Village Secretary, Village Government Program Management, Village Governance